Yoghurt consumption regulates the immune cells implicated in acute intestinal inflammation and prevents the recurrence of the inflammatory process in a mouse model - Chaves, Analia Silvina (2011)
Crohn's disease and ulcerative colitis, two forms of inflammatory bowel disease, are important problems in industrialized countries. The complete etiology of these two diseases is still unknown but likely involves genetic, environmental, and immunological factors. The aim of the present work was to determine whether the anti-inflammatory effects reported for yoghurt in acute trinitrobenzene sulfonic acid-induced intestinal inflammation in mice also could prevent or attenuate the recurrent intestinal inflammation, thus maintaining remission. The innate response also was evaluated through participation of Toll-like receptors (TLRs) and the analysis of T-cell populations to determine the effects of yoghurt in an acute inflammatory bowel disease model. Yoghurt exerted a beneficial effect on acute intestinal inflammation by regulating T-cell expansion and modulating the expression of TLRs, with decrease of TLR4+ and increase of TLR9z cells. The anti-inflammatory effect of yoghurt also was demonstrated in a recurrent inflammation model. Yoghurt administration during the remission phase prevented the recurrence of inflammation without producing undesirable side effects. The yoghurt effect may be mediated by increased interleukin 10 production and changes in intestinal microbiota.